2019
DOI: 10.1155/2019/7207012
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum Results on Differing Degrees of Ketonuria in Nulliparous Women with Gestational Diabetes Mellitus during Spontaneous Labor

Abstract: To compare intrapartum results associated with differing degrees of ketonuria in nulliparous women with gestational diabetes mellitus (GDM), we implemented a retrospective cohort study comparing clinical characteristics among differing degrees of ketonuria and the duration and distribution of ketonuria at different stages of labor. We also analyzed adverse maternal and neonatal outcomes for each group. A total of 570 GDM deliveries were included; of these, 238 had negative ketonuria (41.8%), 180 had moderate k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Follow-up of the patient with GDM Throughout the pregnancy, the patient is monitored by a multidisciplinary medical team. Monitoring includes glycemic control, HbA1C, weight gain, assessment of kidney function by creatinine clearance and albuminuria, ketonuria, blood pressure measurement and ophthalmological control [65].…”
Section: Insulin Therapymentioning
confidence: 99%
“…Follow-up of the patient with GDM Throughout the pregnancy, the patient is monitored by a multidisciplinary medical team. Monitoring includes glycemic control, HbA1C, weight gain, assessment of kidney function by creatinine clearance and albuminuria, ketonuria, blood pressure measurement and ophthalmological control [65].…”
Section: Insulin Therapymentioning
confidence: 99%
“…In 2018, Huang et al monitored and recorded the urinary ketones and delivery results of 570 pregnant women with GDM during childbirth and found that maternal ketonuria is quite common in women with GDM who have not given birth. 26 According to the different urine ketone content, 570 subjects were divided into three groups: negative, moderate ketonuria and ketosis. By comparing the birth complications between different urine ketone levels, Huang SY et al found that incidences of FHR III, third-degree amniotic fluid contamination, and postpartum hemorrhage increased with the development of ketonuria.…”
Section: Relationship Between Abnormal Ketone Body Levels and Differementioning
confidence: 99%